FORMATION AND DEVELOPMENT OF THE FINANCIAL POTENTIAL OF TOURISM AND HOSPITALITY INSTITUTION - YUDINA, Olena; STEBLIUK, Nataliia; IVANTSOV, Serhii; VASKOVA, Darya (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article highlights the peculiarities of the formation and development of the financial potential of an institution in the field of tourism and hospitality. The purpose of the study was to study the theoretical and methodological foundations of the formation and development of the financial potential of an institution in the field of tourism and hospitality. The financial model of the institution of tourism and hospitality (restaurant), which is a key tool for managing the institution's financial potential, has been determined. The break-even point is calculated, which is an important indicator for business. It has been established that substantiating a business idea is an important step to ensure success in opening a tourism and hospitality establishment and developing its financial potential. Along with the justification of financial stability and market demand, the justification of the business idea of the institution also includes the analysis of operational aspects. This includes studying the location, organizational structure, supply chain, potential problems and challenges related to personnel management, menu development and ensuring high quality service. The justification of these aspects helps to understand how to ensure efficient and profitable operation of the institution, to attract and satisfy customers, as well as to ensure a high reputation and competitiveness in the market.
Keywords: financial potential; institution; tourism and hospitality sphere; formation; development; business idea